(untitled) (Eurasian Scientific Herald, 2023)
From 2019 to 2022, 140 patients with degenerative diseases of the spine were examined at the neurosurgical department of the clinics of the ASMI. During surgery, samples of the ligamentum flavum were taken for pathomorphological examination and to study the underlying changes. This study studied the pathomorphological changes that develop in the yellow ligament of the spinal canal in all types of degenerative diseases of the lumbar spine. Yellow body fragments covering the posterior border of the spinal canal were taken as Material. The results show that in some degenerative diseases of the lumbar spine, the yellow ligament has only undergone hypertrophy, while in others it has developed dystrophy, limescale, and in others it has ossification and deformity. Developing after hypertrophy, thickening, degenerative and inflammatory diseases of the yellow ligament of the spine, it begins with an increase in cysticitra cells around the blood vessels and in the intermediate tissue. Hypertrophy of the yellow ligament shows a sharp increase in collagen fibers, the development of the fibroelastosis process, the breakdown and destruction of elastic fibers, and a decrease in the amount of bialn.